Mycorrhizal-Bacterial Amelioration of Plant Abiotic and Biotic Stress - Santoyo, Gustavo; Gamalero, Elisa; Glick, Bernard R. (Frontiers in Sustainable Food Systems, 2021)
Soil microbiota plays an important role in the sustainable production of the different types of agrosystems. Among the members of the plant microbiota, mycorrhizal fungi (MF) and plant growth-promoting bacteria (PGPB) interact in rhizospheric environments leading to additive and/or synergistic effects on plant growth and heath. In this manuscript, the main mechanisms used by MF and PGPB to facilitate plant growth are reviewed, including the improvement of nutrient uptake, and the reduction of ethylene levels or biocontrol of potential pathogens, under both normal and stressful conditions due to abiotic or biotic factors. Finally, it is necessary to expand both research and field use of bioinoculants based on these components and take advantage of their beneficial interactions with plants to alleviate plant stress and improve plant growth and production to satisfy the demand for food for an ever-increasing human population.